Kinetic characterization of bile salt transport by human NTCP (SLC10A1). (February 2018) - Jani, Márton; Beéry, Erzsébet; Heslop, Teresa; Tóth, Beáta; Jagota, Bhavana; Kis, Emese; Kevin Park, B.; Krajcsi, Peter; Weaver, Richard J.
Abstract: The transport of bile acids facilitated by NTCP is an important factor in establishing bile flow. In this study, we examine the kinetics associated with human NTCP-dependent transport of two quantitatively important bile acids comprising the human bile acid pool, chenodeoxycholic acid and glycine-chenodeoxycholate, and secondary bile salt, 3-sulfo-glycolithocholate of potential toxicological significance. The study employed human NTCP overexpressing Chinese Hamster Ovary cells and results compared with taurocholate, a prototypical bile salt commonly used in transporter studies. GCDC and 3S-GLC but not CDCA were transported by NTCP. The efficient uptake of GCDC, TCA and 3S-GLC by NTCP enabled the determination of kinetics. GCDC displayed a lower KM (0.569 ± 0.318 μM) than TCA (6.44 ± 3.83 μM) and 3S-GLC (3.78 ± 1.17 μM). The apparent CLint value for GCDC was 20-fold greater (153 ± 53 μl/mg protein/min) than the apparent CLint for TCA (6.92 ± 4.72 μl/mg protein/min) and apparent CLint for 3S-GLC (8.05 ± 1.33 μl/mg protein/min). These kinetic results provide important complementary data on the substrate selectivity and specificity of NTCP to transport bile acids. NTCP transports GCDC with greater efficiency than TCA and has the same efficacy for 3S-GLC and TCA. Highlights: Human membrane NTCP protein transports 3S-GLC and TCA with similar KM and Vmax . Kinetics of GCDC uptake by human NTCP is more efficient than TCA. CDC is not transported by NTCP. 3S-GLC transport by human NTCP has implications in certain groups of patients.